Development of STEAM-Based Rain Alarm Prototype - Mila Candra Pristianti; Eko Hariyono; Desi Wulandari (Indonesia Approach Education, 2022)
The sudden changes in weather and unpredictable rain have an impact on human life. The objective of this research is to analyze the effectiveness and sensitivity of a rain alarm prototype and its relationship with STEAM. This study employs the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations). Then, the benefits will be applied in student learning by teachers through global warming education with an environmental awareness theme. From this research, the following findings were discovered: 1) The rain alarm prototype has a high effectiveness, where each component used was successfully processed and utilized; 2) the sensitivity level revealed that the water, temperature, and humidity sensors have high sensitivity; 3) the relationship between the prototype and STEAM lies in the science aspect, as measured parameters were approached scientifically, the technology aspect through the utilization of the ThingSpeak application, engineering aspect through the collaboration of three different sensors (water, temperature, humidity), and analyzing their contributions in the field of classroom learning. In terms of art, the sensor components are neatly packaged and a housing is also created as an example of installation. Mathematics is found in the coding within the Arduino application. However, a limitation of the research is the inability to utilize an automatic roof system, which means that it cannot automatically lift snacks/clothes during rainfall. Therefore, future research can further develop this prototype by incorporating an automatic roof system.